ANALISIS KUALITAS HASIL PRAKTEK KEMEJA PRIA PADA MATA KULIAH BUSANA PRIA - Rina Purwanti; Ari Eko Budiyanto (Journal of Social Sustainability Management, 2022)
This study aims to analyze the quality of the results of the practice of men's shirts in menswear courses. Analysis of the results of men's shirt practice seen from several aspects including stitching, size, shape, pressing. For the stitches to be analyzed, namely neat stitches, not wavy, good seams with balanced tension of the bottom thread and top thread, the size of the men's shirt must fit between the stitches with an error tolerance pattern of approximately two mm, the shape referred to in this study is the symmetrical shape between right and left collar, right and left shoulder and right and left side, the collar must be sharp and neat, pressing must be done carefully because if it is not done according to the procedure it can cause the material to be pressed by attaching hard cloth or flicelin to wavy. The results of learning to make men's shirts are reviewed from various aspects including aspects of stitching, size, shape, pressing and material selection. Regarding the results of research on making men's shirts in fourth semester students of the Fashion Design Vocational Education Study Program in learning to make men's shirts as a whole, they were in a good/appropriate position, namely 47.05%. This shows that most students have good abilities in understanding any material given by lecturers in practice. This is proven by the practical work that is done, the results are very satisfying, the results are neat stitches, appropriate patterns, and good designs. The learning process for making men's shirts has gone quite well and smoothly, this is shown from the results of the practicum conducted by students. However, it still has to carry out development and improvement in order to improve the quality of learning outcomes.